Efektivitas Media Kincir Angin untuk Melatih Maharah Qiro'ah dalam Pembelajaran Bahasa Arab Siswa PAUD dan Pembelajaran BTQ (Baca Tulis Qur'an) Siswa TPA serta Pentingnya Literasi Ekonomi Islam terhadap Usaha Mikro Kecil dan Menengah (UMKM) - M. Taufiq Arkan; Bernan Dwi Atmojo; Tiara Pelangi Arafah; Ahmad Hudaebiah; Fadly Alfarissy; Muhammad Zakaria; Humairo Azizah; Muhammad Akmal Faqih; Alvie Muthia Putri; Moetiah Annisa Roestam; Deliana Suwita (Jurnal Pustaka Cendekia Pendidikan, 2024)
Community empowerment is an important form of program in increasing community participation. The implementation of empowerment will be more effective and efficient with the role of government, community, academics and other supporting parties. In particular, the role of universities in empowering communities with KKN programs is also applied at Muhammadiyah University, Prof. DR. HAMKA as KKS. Based on the level of crisis occurring in society, the theme of Community Empowerment Education by Instilling Islamic Knowledge and Sharia Economics was determined. The KKS program is implemented on Jl. Bunga Rampai VI Gang 1 Rt.017 Rw.09, Malaka Jaya, Kec. Duren Sawit, East Jakarta City Prov. D.K.I. Jakarta. There are main programs and assistance programs in this KKS activity. The main work program consists of the field of educational empowerment and the field of sharia economics. The assistance work program consists of organizing local RT/RW information posts. The implementation of the main work program and assistance received a positive response and there was even active participation from the RT Head, RW Head, children in the Malakasari sub-district so that everything went smoothly and there was even a special request to continue the program from the KKS group.